Pemasangan Akses Internet dan Pemanfaatan Antena Mikrostrip Untuk Membantu UMKM di Kampung Setaman, Cipayung, Depok - Kurniawati, Nazmia; Nixon, Benny; Rafsyam, Yenniwarti; Danaryani, Sri; Fahmi, Ahdiyat; Raihan, Muhammad (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2023)
Kampung Setaman, which is located in Kelurahan Ratujaya, is an area where the majority of the people are Micro, Small and Medium Enterprises (MSMEs). Internet access is an important aspect for people to sell their products. In this community service activity, Politeknik Negeri Jakarta (PNJ) Telecommunication Study Group (KBK) carried out internet installation and coverage area expansion using a microstrip antenna. This aims to ensure that people can enjoy internet access in a wide area without requiring the installation of many access points. There are two installation points, namely Posyandu Kartini 2 and Jami Al-Huda Mosque. The microstrip antenna is made in the form of a 1x4 square patch. From the measurement results, by using the created antenna the access point can reach a distance of up to 115 m with Line of Sight (LOS) conditions. As a result of the installation, people can enjoy free internet access in a wide area.